FOOD SAFETY STANDARDS AND LAW OF THE WORLD TRADE ORGANIZATION - Divljak, Drago (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The paper discusses the legal significance of food safety standards in the WTO. In this framework, the task is to determine the formal normative basis and conceptual approach to this issue. The subject of more detailed analysis will be the essential determinants of this approach, in particular the process of harmonization and the status of international standards in the WTO law. In addition, the paper aims to determine the effective results of the WTO rules in this area, as well as their scope and limitations, and this especially refers to the process of harmonization and application of international standards. In the area of food safety, in the WTO law, through the Agreement on the Application of Sanitary and Phytosanitary Measures, a realistic normative system is created based on the rules that ensure safety and predictable access to food at the international market, with priority observing of human health and food safety. In terms of content, the leading role of states in this area is not excluded, but it is upgraded with alternative solutions for the facilitated development of international trade, in particular with a strong fostering of harmonization and normative recognition and regulation of the status of international standards. Although the given WTO approach can certainly be positively evaluated, it is not unambiguous and faces limitations and challenges, especially in the context of the Codex of standards as the main international reference point in the field of food safety. Therefore, it is necessary to refine this normative system, harmonize it one with another, and specifically specify it in order to avoid negative implications of the vagueness of some of the rules, which would raise the effectiveness of these rules to a higher level.